Parasite microtubule arrays - Ferreira, Josie; Frischknecht, Friedrich (Current biology, 2023)
Microtubules are a key component of eukaryotic cell architecture. Regulation of the dynamic growth and shrinkage of microtubules gives cells their shape, allows cells to swim, and drives the separation of chromosomes. Parasites have developed intriguingly divergent biology, seemingly expanding upon and reinventing microtubule use in fascinating ways. These organisms affect life on the planet at scales that are often overlooked: there are likely more parasitic than free-living organisms on Earth, and they have a sizeable influence across ecosystems. As parasites can cause devastating diseases, this in turn drives evolutionary adaptations and species diversity. Parasites are varied, living in all environments and at all scales — from the tiny 2 μm single-celled Plasmodium merozoite that invades red blood cells to the 40 m long Tetragonoporus, a large intestinal tapeworm of whales. To survive in their various niches, parasites have undergone striking adaptations and developed complex life cycles, often involving two or more host species. This diversity is reflected at the cellular level, where unique molecular mechanisms, cytoskeletal structures and organellar compositions are found. Hence, the study of parasite cell biology provides a biological playground for understanding diversity and species diversification. It also facilitates the identification of specific targets to develop urgently needed therapeutics: for example, drugs targeting microtubules are used at large scale to treat intestinal worms and parasites that form tissue cysts in our livers and brains. Here, we discuss some of the curious microtubule arrays found in a small, select number of human-infecting, single-celled parasites of medical importance (Table 1). Our aim is to put a spotlight on distinctive molecular features in a field that promises exciting cell-biological discoveries with the potential for therapeutic breakthroughs.